The Influence of Brand Image and Promotion on Purchase Decisions of Belikopi Products at MERR Pandugo Surabaya with Word of Mouth as a Mediation Variable - Yayang Pitino; Endah Budiarti (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This research aims to evaluate the impact of brand image and promotion on purchasing decisions for Belikopi products at Merr Pandugo Surabaya. The word-of-mouth variable is the mediator in this research. A total of 100 respondents who had purchased and tasted Belikopi products in Surabaya participated in data collection through questionnaires. The method used to analyze this research is Structural Equation Modeling (SEM) with the application of the Partial Least Squares (PLS) mediation test tool to test the relationship between variables in the conceptual framework that has been prepared